Germaniens Lobpreis bei Aeneas Sylvius und Nicolaus Cusanus: Ein historisch-geographischer Beitrag zur ältesten Mitteleuropakarte - Schmidt, Johanna (ERDKUNDE, 1953)
On the basis of a detailed interpretation of sources, the author proves that the description of Modern Germania (2nd part), accompanying Nicolaus Cusanus’s map of Middle Europe agrees to a very large extent in meaning and vocabulary with the praise of Germania by Aeneas Silvius, and is in the last instance to be attributed to him. That hymn is at the same time a historic-geographical document showing the importance of Germania in the Europe of the day.